Proof: Three Angles

Let's prove the following theorem:

if the following are true:
  • 60 + (a2) = 180
  • not (2 = 0)

then a = 60

Proof:

View as a tree | View dependent proofs | Try proving it

Given
1 60 + (a2) = 180
2 not (2 = 0)
Proof Table
# Claim Reason
1 a2 = 180 + (60 ⋅ (-1)) if 60 + (a2) = 180, then a2 = 180 + (60 ⋅ (-1))
2 180 + (60 ⋅ (-1)) = 120 180 + (60 ⋅ (-1)) = 120
3 a2 = 120 if 180 + (60 ⋅ (-1)) = 120 and a2 = 180 + (60 ⋅ (-1)), then a2 = 120
4 a = 120 / 2 if not (2 = 0) and a2 = 120, then a = 120 / 2
5 120 / 2 = 60 120 / 2 = 60
6 a = 60 if 120 / 2 = 60 and a = 120 / 2, then a = 60

Comments

Please log in to add comments